Financial literacy and financial technology on the personal finance behavior of generation z - Perawati, Perawati; Juniwati, Juniwati; Malini, Helma; Azazi, Anwar; Mustika, Uray Ndaru (Junal Ilmu Manajemen, 2025)
The Indonesian economy is experiencing significant expansion, driven by technological advancements, with financial literacy being crucial to enhancing understanding and financial education among Generation Z in West Kalimantan. The present research aims to examine the influence of financial literacy on the personal financial behavior of Generation Z, both directly and via lifestyle as a mediating variable, while also analyzing the direct impact of financial technology on their personal finances. This study employed a qualitative research technique utilizing a causal associative method, involving a sample of 247 respondents from Generation Z in West Kalimantan. Data were gathered via surveys and analyzed via structural equation modelling (SEM) with SmartPLS 4.0 software. Research findings indicate that financial literacy has a positive and significant influence on the personal finance behavior of Generation Z, with lifestyle serving as an effective mediator. The results underscore the significant of financial literacy and lifestyle in influencing improved financial behavior among Generation Z, with implications for developing more effective financial education programs.